Building an Information System Design Theory for Vigilant EIS - Walls, Joseph G.; Widmeyer, George R.; El Sawy, Omar A. (Information Systems Research, 1992)
This paper defines an information system design theory (ISDT) to be a prescriptive theory which integrates normative and descriptive theories into design paths intended to produce more effective information systems. The nature of ISDTs is articulated using Dubin's concept of theory building and Simon's idea of a science of the artificial. An example of an ISDT is presented in the context of Executive Information Systems (EIS). Despite the increasing awareness of the potential of EIS for enhancing executive strategic decision-making effectiveness, there exists little theoretical work which directly guides EIS design. We contend that the underlying theoretical basis of EIS can be addressed through a design theory of vigilant information systems. Vigilance denotes the ability of an information system to help an executive remain alertly watchful for weak signals and discontinuities in the organizational environment relevant to emerging strategic threats and opportunities. Research on managerial information scanning and emerging issue tracking as well as theories of open loop control are synthesized to generate vigilant information system design theory propositions. Transformation of the propositions into testable empirical hypotheses is discussed.